The Influence of Organizational Culture on Employee Performance Moderated by Work Environment At The Cooperative, SMEs, Industry, and Trade Office of Bungo Regency - Khairun A Roni; Sella Devi Oktaviani; Yudhi Novriansyah; Supriyati Supriyati; Herawati Herawati (ProBisnis : Jurnal Manajemen, 2025)
The purpose of this study is to determine the influence of Organizational Culture on Employee Performance, moderated by the Work Environment, at the Bungo District Cooperative, Small and Medium Enterprises, Industry, and Trade Office. Using an Associative research method and Quantitative analysis with Smart PLS 4.0 statistics on 34 research respondents. The research results directly show that Organizational Culture (X) and Work Environment (Z) significantly influence Employee Performance (Y). However, indirectly, the Work Environment (Z) is unable to moderate or weaken the influence of Organizational Culture (X) on Employee Performance (Y). The conclusion of the study is that paying attention to a conducive work environment will impact maximum work performance.